Integrated Crop Management in Sustainable Agriculture - Hussain, Mubshar; Ul-Allah, Sami; Farooq, Shahid (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Integrated crop management involves several eco-friendly measures combined to sustain production. The integration of these management practices leads to improved soil health and crop productivity. However, the benefits of Integrated Crop Management are largely influenced by the environment, soil type and fertility, and crop type. Mono-cropping systems or the use of the same crop rotation have led to reduced soil quality, favoring insect pest infestation and reducing farm profits. This Special Issue focuses on the impacts of Integrated Crop Management practices on soil health, crop productivity, and a reduction in the impacts of expected climate change on crop production in a sustainable manner.